Economic analysis of Agaricus bisporus mushrooms production and the perspective of sharing economy - Schilla, Filip; Prochazka, Petr; Mumladze, Gaga; Soukupova, Jana; Smutka, Lubos (Frontiers in Sustainable Food Systems, 2025)
In the face of climate change, land scarcity, and food security concerns, innovative and sustainable approaches to agriculture are imperative. Urban agriculture, particularly the cultivation of mushrooms in basement conditions, emerges as a promising solution to address these multifaceted challenges. This article explores the viability and benefits of basement cultivation of Agaricus bisporus mushrooms as a sustainable response to climate change, land scarcity, and food security. The topic is also discussed as a possible example for a sharing economy business model. Within the paper simulated basement and ground level room space conditions are created and conditions are compared to each other with economic calculations.